Association of low serum albumin concentration and adverse cardiovascular events in stable coronary heart disease. (15th August 2017) - Chien, Shih-Chieh; Chen, Chun-Yen; Leu, Hsin-Bang; Su, Cheng-Huang; Yin, Wei-Hsian; Tseng, Wei-Kung; Wu, Yen-Wen; Lin, Tsung-Hsien; Chang, Kuan-Cheng; Wang, Ji-Hung; Wu, Chau-Chung; Yeh, Hung-I; et al.
Abstract: Objective: Coronary heart disease (CHD) is a leading cause of death in developed countries. Exploration of indicators to identify high risk individuals who develop adverse outcomes despite stable baseline condition is important. This study is to evaluate the association between serum albumin concentration and cardiovascular (CV) outcomes in individuals of stable CHD. Methods: Seven-hundred–thirty-four participants from Biosignature study, a nationwide prospective cohort study aimed to identity risk factors among patients with stable CHD, were enrolled for analysis. They were divided into low serum albumin group (baseline albumin concentration < 3.5 g/dL, n = 98) and normal albumin group (baseline albumin concentration ≥ 3.5 g/dL, n = 636). The relations between baseline albumin and adverse CV outcomes within 18 months of follow-up were analyzed. Results: Compared baseline characteristics with normal albumin group, subjects in low albumin group are older, having more diabetic patients, lower hemoglobin level, lower estimated glomerular filtration rate, lower total cholesterol level, lower left ventricular ejection fraction, and higher blood glucose. While there is no significant difference of total CV events between two groups, low serum albumin concentration is associated with an increased risk of all-cause mortality (10.2% vs. 0.5%, p < 0.001) and hard CV events (7.1% vs. 1.4%, p < 0.001). The association remains significant after adjustments for confounders (all-cause mortality, HR: 6.81, 95% CI: 1.01–45.62; hard CV events, HR: 3.68, 95% CI: 1.03–13.19). Conclusions: Low serum albumin concentration (< 3.5 g/dL) worsens prognosis of patients with stable CHD.